Promoting help-seeking using e-technology for ADolescents with mental health problems: study protocol for a randomized controlled trial within the ProHEAD consortium$Michael Kaess, Sabrina Ritter, Sophia Lustig, Stephanie Bauer, Katja Becker, Heike Eschenbeck, Markus Moessner, Christine Rummel-Kluge, Hans-Joachim Salize, Rainer Thomasius, Franz Resch, Julian Koenig and the ProHEAD consortium - Kaess, Michael; Ritter, Sabrina; Lustig, Sophia; Resch, Franz; Koenig, Julian; Bauer, Stephanie; Moessner, Markus; Salize, Hans Joachim (Trials, 2019)
The highest incidence and prevalence of mental health problems across the lifespan as well as the first onset of most long-term mental health conditions are reported for youths between 14 and 25 years of age. At the same time, only 25% of adolescents with mental health problems receive professional treatment. One explanation for poor treatment access in youths is their low help-seeking behavior. Barriers that can keep children and adolescents (C&A) from seeking professional help include a lack of perceived need, structural barriers, or stigma. Interventions based on e-technology might present an effective approach, overcoming these barriers by reducing stigma and providing low-threshold access with enhanced reach, ultimately facilitating help-seeking for mental health problems among youths.